Exercise after Heart Transplantation: Typical Alterations, Diagnostics and Interventions - Schmidt, Thomas; Bjarnason-Wehrens, Birna; Predel, Hans-Georg; Reiss, Nils (International Journal of Sports Medicine, 2020)
For the treatment of terminal heart failure, heart transplantation is considered to be the gold standard, leading to significantly improved quality of life and long-time survival. For heart transplant recipients, the development and maintenance of good functional performance and adequate exercise capacity is crucial for renewed participation and integration in self-determined live. In this respect, typical transplant-related alterations must be noted that play a significant role, leading to restrictions both centrally and peripherally. Before patients begin intensive and structured exercise training, a comprehensive diagnosis of their exercise capacity should take place in order to stratify the risks involved and to plan the training units accordingly. Particularly endurance sports and resistance exercises are recommended to counter the effects of the underlying disease and the immunosuppressive medication. The performance level achieved can vary considerably depending on their individual condition, from gentle activity through a non-competitive-level to intensive competitive sports. This paper includes an overview of the current literature on heart transplant recipients, their specific characteristics, as well as typical cardiovascular and musculoskeletal alterations. It also discusses suitable tools for measuring exercise capacity, recommendations for exercise training, required precautions and the performance level usually achieved.
Keywords: heart failure; heart transplantation; transplant-related alterations; exercise testing; exercise training; exercise capacity